Single response assessment of transplant-ineligible multiple myeloma: a supplementary analysis of JCOG1105 (JCOG1105S1). (6th May 2021) - Nakamura, Nobuhiko; Maruyama, Dai; Machida, Ryunosuke; Ichinohe, Tatsuo; Takayama, Nobuyuki; Ohba, Rie; Ohmachi, Ken; Imaizumi, Yoshitaka; Tokunaga, Masahito; Katsuya, Hiroo; Yoshida, Isao; Sunami, Kazutaka; et al.
Abstract: Background: The International Myeloma Working Group response criteria require two consecutive assessments of paraprotein levels. We conducted an exploratory analysis to evaluate whether a single response assessment could be a substitute for the International Myeloma Working Group criteria using data from JCOG1105, a randomized phase II study on melphalan, prednisolone and bortezomib. Methods: Of 91 patients with transplant-ineligible newly diagnosed multiple myeloma, 79 patients were included. We calculated the kappa coefficient to evaluate the degree of agreement between the International Myeloma Working Group criteria and the single response assessment. Results: Based on the International Myeloma Working Group criteria, 11 (13.9%), 20 (25.3%), 36 (45.6%) and 12 (15.2%) patients had stringent complete response/complete response, very good partial response, partial response and stable disease, respectively. Based on the single response assessment, 17 (21.5%), 19 (24.1%), 35 (44.3%) and 8 (10.1%) patients had stringent complete response/complete response, very good partial response, partial response and stable disease, respectively. The kappa coefficient was 0.76 (95% confidence interval, 0.65–0.88), demonstrating good agreement. The single response assessment was not inferior to the International Myeloma Working Group criteria in the median progression-free survival (3.8 and 2.9 years) in stringent complete response/complete response patients, suggesting that the single response assessment was not an overestimation. Conclusions: The single response assessment could be a substitute for the current International Myeloma Working Group criteria for transplant-ineligible newly diagnosed multiple myeloma. Abstract : The single response assessment could be a substitute for the current International Myeloma Working Group criteria with two consecutive assessments in patients with transplant-ineligible newly diagnosed multiple myeloma.